Channel MAC Protocol for Opportunistic Communication in Ad Hoc Wireless Networks. (7th August 2008) - Ashraf Ashraf, Manzur Manzur; Jayasuriya Jayasuriya, Aruna Aruna; Perreau Perreau, Sylvie Sylvie
Abstract : Despite significant research effort, the performance of distributed medium access control methods has failed to meet theoretical expectations. This paper proposes a protocol named "Channel MAC" performing a fully distributed medium access control based on opportunistic communication principles. In this protocol, nodes access the channel when the channel quality increases beyond a threshold, while neighbouring nodes are deemed to be silent. Once a node starts transmitting, it will keep transmitting until the channel becomes "bad." We derive an analytical throughput limit for Channel MAC in a shared multiple access environment. Furthermore, three performance metrics of Channel MAC—throughput, fairness, and delay—are analysed in single hop and multihop scenarios using NS2 simulations. The simulation results show throughput performance improvement of up to 130% with Channel MAC over IEEE 802.11. We also show that the severe resource starvation problem (unfairness) of IEEE 802.11 in some network scenarios is reduced by the Channel MAC mechanism.